A novel role for nonactin: interfering with G-quadruplex in RET-driven medullary thyroid cancer - Tariq Alqahtani; Arwa Alsubait; Meshari Aloumi; Abdulrahman Alamer; Ghala Alomari; Osama I. Alwassil; Ahmad J. Obaidullah; Sahar S. Alghamdi (BMC Cancer)
Abstract Background Medullary Thyroid Carcinoma (MTC) is closely associated with mutations in the RET proto-oncogene, placing the activated RET protein at the center of MTC pathogenesis. Existing therapeutic solutions, primarily tyrosine kinase inhibitors such as selpercatinib, vandetanib, and cabozantinib, have shown moderate efficacy but are accompanied by increased risks of side effects and resistance. This study unveils a promising avenue using nonactin, a compound historically recognized for its antibacterial properties, targeting the G-quadruplex interactions within the RET proto-oncogene. Method In this research, high-throughput screening was conducted using a luciferase reporter-based cellular assay. The MTC TT cell line was treated with nonactin for 24 and 48 h. Immunoblotting and RT-PCR were employed to measure the protein and RNA levels of RET and its downstream stream proteins. Binding to the G-Quadruplex was assessed using melting curves and Circular Dichroism. The cell cycle was analyzed using FACS, and caspase activity was measured to indicate the activation of apoptosis. Results Nonactin was identified to significantly reduce luciferase activity driven by the RET promoter. A deeper exploration revealed nonactin's remarkable selectivity against tumor cell lines harboring RET mutations, effectively inducing apoptosis. Nonactin was also found to bind to the G-quadruplex region on RET. Conclusion The findings highlight the compound's therapeutic potential, emphasizing its mechanism of inducing apoptosis in active mutant RET cell lines by interacting with G-quadruplex structures. This novel insight opens avenues for a potentially effective treatment for MTC, potentially bypassing the challenges associated with current TKIs.